2021
DOI: 10.3168/jds.2020-19956
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life of Domiati cheese under modified atmosphere packaging

Abstract: The present study describes the effects of modified atmosphere packaging (MAP) on shelf-life extension, chemical, microbiological, and sensory properties of Domiati cheese. Five different MAP were studied [10% CO 2 /90% N 2 (G1), 15% CO 2 /85% N 2 (G2), 25% CO 2 /75% N 2 (G3), 100% CO 2 (G4), and 100% N 2 (G5)]. Control samples were packaged in air (CA) and under vacuum. In both groups of cheeses, chemical analysis was significantly affected by MAP during cold storage. Ripening indexes were significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…However, when the scores of the E group were evaluated within themselves, significant differences were obtained (P<0.05). The findings obtained in this study are similar to the findings of some researchers (Marcuzzo et al, 2012;Acerbi et al, 2018;Darnay et al, 2019, Atallah et al, 2021.…”
Section: Sensory Resultssupporting
confidence: 92%
“…However, when the scores of the E group were evaluated within themselves, significant differences were obtained (P<0.05). The findings obtained in this study are similar to the findings of some researchers (Marcuzzo et al, 2012;Acerbi et al, 2018;Darnay et al, 2019, Atallah et al, 2021.…”
Section: Sensory Resultssupporting
confidence: 92%
“…A decrease in the O2 level from 19.98% to 0.16% was detected in previous experiences when dealing with Domiati cheese in cold air storage, despite using a very high oxygen barrier packaging film [37]. A decrease in the O 2 level from 19.98% to 0.16% was detected in previous experiences when dealing with Domiati cheese in cold air storage, despite using a very high oxygen barrier packaging film [37].…”
Section: Headspace Gas Compositionmentioning
confidence: 79%
“…Indeed, it has been reported that CO 2 concentrations below 20% do not inhibit the growth of moulds [21,47]. Short storage times have been described for cheeses kept in air on account of mould growth [22,37,48]. MAP1 and MAP2 showed no significant changes for texture, flavour, and paste holes during the 56 storage days.…”
Section: Sensory Analysismentioning
confidence: 96%
“…The total aerobic mesophilic bacterial count was carried out in a plate count agar (Oxoid) incubated at 30 • C for 48 h, and at 5 • C for 10 days for total psychrotrophic bacteria [25]. Coliform bacteria were observed by APHA [26].…”
Section: Microbiological Propertiesmentioning
confidence: 99%